A NARRATIVE REVIEW ON NEURALLY MEDIATED SYNCOPE - Kumar, Ranjan (Student’s Journal of Health Research Africa, 2023)
In this correspondence, we aim to provide a comprehensive analysis of the pathophysiology underlying reflex syncope, encompassing vasovagal syncope, carotid sinus syndrome, and situational syncope. Additionally, we seek to enhance understanding by offering clarification on the terminology employed in this context.